UTILIZATION OF CASHEW FRUIT ABON TO INCREASE FARMERS' INCOME - Sintayana Muhardini; Raden Sudarwo; Ibrahim Ibrahim; Kamaladini Kamaladini; Zuhratul Azizah; Titik Hariani (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Banyaknya buah jambu mete yang tidak dimanfaatkan dengan baik, serta laju pertumbuhan penduduk yang terus meningkat yang membuat masyarakat Karang Bajo sulit mempeoleh pekerjaan. Tujuan kegiatan ini adalah pengenalan dan pelatihan pembuatan abon sebagai produk olahan dari daging jambu mete untuk masyarakat Desa Karang Bajo Kecamatan Bayan. Program dilaksanakan secara daring via zoom meeting, dengan tahapan; identifikasi, persiapan, pelaksanaan, evaluasi, dan pembuatan laporan. Hasil kegiatan memberikan pengetahuan baru kepada warga yang ada terutama ibu-ibu. Keberlanjutan program ini dengan terbentuknya UMKM yang bertujuan untuk mengembangkan usaha abon jambu mete. Adanya UMKM guna mewadahi masyarakat Karang Bajo terutama ibu-ibu untuk tetap melakukan kegiatan pembuatan abon daging jambu mete untuk menambah penghasilan.Abstract: The number of cashews that are not utilized properly, as well as the increasing rate of population growth that makes it difficult for the people of Bajo reef to get jobs. The purpose of this activity is the introduction and training of making abon as a processed product of cashew nut meat for the people of Karang Bajo Village, Kecematan Bayan. The program is carried out online via zoom meeting, with stages; identification, preparation, implementation, evaluation, and report making. The results of the activities provide new knowledge to existing residents, especially mothers. The sustainability of this program with the formation of MSMEs that aim to develop cashew abon business. The existence of MSMEs to accommodate the Bajo coral community, especially mothers to continue making cashew meat abon to increase income.